О перспективах нефтегазового поиска на глубине 8000–12500 м в Днепровско-Донецкой впадине - Гожик, П.Ф.; Краюшкин, В.А.; Клочко, В.П. (Видавничий дім "Академперіодика" НАН України, 2007)
The abyssal petroleum potential is tremendous. It is shown on many drilling results at depths from 8,000 to 12,500 m where there are already 20 giant oil and oil-gas fields, as well as in a light of the modern Russian-Ukrainian theory about the abyssal inorganic origin of petroleum in the Earth's mantle.